Reliable assessment of the effects of treatment on mortality and major morbidity, II: observational studies. - MacMahon, S; Collins, R (2001)
Observational studies and randomised trials can contribute complementary evidence about the effects of treatment on mortality and on major non-fatal outcomes. In particular, observational studies have an important role in the identification of large adverse effects of treatment on infrequent outcomes (ie, rare, but serious, side-effects) that are not likely to be related to the indications for (or contraindications to) the treatment of interest. Such studies can also provide useful information about the risks of death and disability in particular circumstances that can help to generalise from clinical trials to clinical practice. But, due to their inherent potential for moderate or large biases, observational studies have little role in the direct assessment of any moderate effects of treatment on major outcomes that might exist. Instead, sufficiently large-scale evidence from randomised trials is needed to assess such treatment effects appropriately reliably. Wider appreciation of the different strengths and weaknesses of these two types of epidemiological study should increase the likelihood that the most reliable evidence available informs decisions about the treatments doctors use--and patients receive--for the management of a wide range of life-threatening conditions.